The "agenda setting" and sources on the radio during and election for the mayor of Bogota, Colombia - Acosta Peña, Raúl Alberto (Universidad de Chile. Instituto de la Comunicación e Imagen, 2015)
The article presents the research results that were carried out during the campaign for mayor of Bogota in Colombia in 2011. Observed in the analysis were the thematic agenda of the media and the sources that journalists used in the creation of the journalistic pieces broadcast on three radio stations (RCN, CARACOL and La W) monitored during their morning newscasts Monday through Friday, excluding holidays. Journalistic genres highlighted in the study are interviews and news. The electoral process subject caught the attention of the media examined. It emphasizes that what most candidates debated about during the campaign was the issue of guarantees or alliances between political parties and campaignsIt is reiterated in the use of just one source, or worse, the lack of journalist sources in the broadcast pieces.